Andean tragedy : fighting the war of the Pacific, 1879-1884 - Sater, William F. (Studies in war, society, and the military., 2007)
The year 1879 marked the beginning of one of the longest, bloodiest conflicts of nineteenth-century Latin America. The War of the Pacific pitted Peru and Bolivia against Chile in a struggle initiated over a festering border dispute. The conflict saw Chiles and Perus armored warships vying for control of sea lanes and included one of the first examples of the use of naval torpedoes.